Conceptualizing and contextualizing with and beyond Paul Hiebert's anthropological models: Toward a contextual trinitarian missiology in Myanmar - Moe, David Thang (Missiology, 2019)
The purpose of this article is threefold. First, it explores Hiebert's critiques of western missionaries' wrong conceptualizations of non-westerners and their non-contextualization and his proposals for the double exegesis of human cultures and the gospel. Second, the article appreciatively and critically evaluates Hiebert's approaches. Finally, the article conceptualizes cultures and contextualizes the gospel with and beyond Hiebert's anthropological models and constructs a contextual trinitarian missiology as the middle ground between cultural anthropology and systematic theology in Myanmar. Thinking with and beyond Hiebert, the article examines three missiological models of how to rightly conceptualize and humbly approach human cultures, and explore the goals of right conceptualizations and humble approaches as the trinitarian grounds and guides for contextualizing the gospel as "good news" for both Christians and others in Myanmar.